THE PRINCIPAL'S STRATEGY IN IMPROVING TEACHER PERFORMANCE AT SMAN 2 UNGGUL ALI HASJMY ACEH BESAR - Riansyah Putra; Murniati Murniati; Niswanto Niswanto (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2021)
The principal's strategy is one of the efforts to improve teacher performance in the learning process. The principal acts as a central force that drives school life, understands the duties and abilities for the success of the school and has a concern. The purpose of this study is to explain the principal's leadership strategy in improving teacher performance at SMAN 2 Unggul Ali Hasjmy, to mention the constraints of the principal's leadership strategy in improving teacher performance at SMAN 2 Unggul Ali Hasjmy, to describe how to overcome the problem of the principal's leadership strategy in improving the performance of SMAN teachers. 2 Superior Ali Hasjmy. The literature review used to analyze the results of this study, namely the Principal's Strategy and Leadership and Teacher Performance and the Principal's Strategy in improving teacher performance. The method used in this research is descriptive-analysis using a qualitative approach, data collection techniques with the stages of observation, interviews and documentation. The research procedure is planning, collecting data, describing, analyzing and concluding. The results of the study, the principal's leadership strategy in improving teacher performance at SMAN 2 Unggul Ali Hasjmy by increasing discipline, providing motivation, being an example for teachers and education staff and conducting supervision. Constraints that occur in the principal's leadership strategy in improving teacher performance at SMAN 2 Unggul Ali Hasjmy, some teachers are late for school, leave earlier than the time specified in the school teaching and learning process, do not improve performance, and the ability of the principal to supervise effectively is one of the problems. One obstacle for school principals is to improve teacher performance.Keywords: Principal Strategy, Teacher Performance